La distinción entre género y voz verbales en las primeras gramáticas del castellano - Iglesias Bango, Manuel (Estudios Humanísticos. Filología, 1990)
There is a certain generalized tendency to think that the problem of voice in Spanish, one way or another, has always been present in the reflections of grammarians ever since the first evidence. However, that way of thinking comes from a confusion caused by the ambiguity of the terms active/passive in the first grammatical texts. In fact, except for some former notes, it can be said that nobody has been fully aware of the matter until the XX’ Century. Up to then, active and passive, when mentioned, refer to a different concept which is not the same as voice: the género verbal (verbal gender).